Hate speech and the harm in Indonesian judicial decisions - Putri, D.K. (Cogent OA, 2023)
Indonesia's hate speech provision under Article 28(2) of the Electronic Information and Transaction Law lacks an objective threshold. This article presents a case study of twenty-seven judicial decisions to investigate whether such lack had consequently limited or instead broadened the judiciary's discretion in determining hate speech. The results of the study show that the construction of Article 28(2) has led to a broad determination of hate speech, as it reveals an inconsistency in considering the harm of hate speech. This paper discusses where the inconsistencies are found and why they are problematic when assessing harm. Furthermore, in light of the case studies, the paper took into perspective the recent development of the Criminal Code to suggest the way forward for Indonesia's law on hate speech.